2020
DOI: 10.1177/1358863x20979738
|View full text |Cite
|
Sign up to set email alerts
|

Association of infrapopliteal medial arterial calcification with lower-limb amputations in high-risk patients: A systematic review and meta-analysis

Abstract: Medial arterial calcification (MAC) is a known risk factor for cardiovascular morbidity. The association between vascular calcifications and poor outcome in several vascular districts suggest that infrapopliteal MAC could be a risk factor for lower-limb amputation (LLA). This study’s objective is to review the available literature focusing on the association between infrapopliteal MAC and LLA in high-risk patients. The PubMed and Embase databases were systematically searched. We selected original studies repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 47 publications
0
11
0
2
Order By: Relevance
“…The extension of medial calcification is associated with an increased mortality risk, irrespective of the revascularization method used [ 23 ]. A meta-analysis, including more than 6500 patients, showed that the presence of MAC on below-knee arteries is associated with a more than two-fold greater risk of lower limb amputation [ 24 ].…”
Section: Clinical Relevance Of Mac In Patients With Padmentioning
confidence: 99%
“…The extension of medial calcification is associated with an increased mortality risk, irrespective of the revascularization method used [ 23 ]. A meta-analysis, including more than 6500 patients, showed that the presence of MAC on below-knee arteries is associated with a more than two-fold greater risk of lower limb amputation [ 24 ].…”
Section: Clinical Relevance Of Mac In Patients With Padmentioning
confidence: 99%
“…Surprisingly, in patients with diabetes, medial arterial calcification is a stronger predictor of cardiovascular mortality compared with intimal calcification [31]. A recent meta-analysis showed that limb amputation is associated with below-the-knee medial arterial calcification [32].…”
Section: Aortic and Peripheral Arterial Disease (Pad)mentioning
confidence: 99%
“… 14 They are also common in the leg arteries in patients with genetic syndromes, renal dysfunction, diabetes, and ageing. 15 Here they predict amputations. A plausible mechanism is that the ‘Windkessel function’ of our arterial system is disturbed by these calcifications and that the high pulse pressure leads to organ failure.…”
Section: Medial Arterial Calcification and Cardiovascular Diseasementioning
confidence: 99%